ANALISIS PENGARUH MODEL PROJECT BASED LEARNING (PjBL) TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Umi Kalsum; Riva Riva (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This investigation was conducted to examine the impact of implementing the Project-Based Learning (PjBL) framework on the educational outcomes of elementary school pupils. Adopting a Systematic Literature Review (SLR) approach, this study scrutinized various scholarly publications centered on the execution of PjBL within primary education settings. The core data were aggregated from 25 national journal articles published spanning the 2020–2025 period. Reference selection adhered to strict inclusion benchmarks: empirical research utilizing PjBL, featuring primary students as the main subjects, and evaluating student performance metrics. Data synthesis was performed through identification, reduction, critical evaluation, and integration of findings from the selected literature. The final insights demonstrate that this project-centric instructional strategy exerts a substantial and favorable influence on enhancing student achievement. The deployment of PjBL successfully fosters cognitive growth, academic drive, ingenuity, analytical thinking, interpersonal communication, teamwork, and troubleshooting capabilities. Furthermore, PjBL surpasses traditional instructional methods in efficiency by promoting an active, situational, and student-centered learning environment. Regarding academic performance, the most pronounced advancement was observed within the cognitive sphere, followed by progressive gains in the affective and psychomotor dimensions. Consequently, the PjBL paradigm serves as a highly viable progressive pedagogical alternative to reinforce the objectives of the Merdeka Curriculum and 21st-century competencies in primary schools. ABSTRAK Investigasi ini dilakukan guna menguji dampak dari implementasi model Project Based Learning (PjBL) terhadap capaian belajar murid di jenjang sekolah dasar. Menggunakan pendekatan Systematic Literature Review (SLR), studi ini menelaah beragam literatur ilmiah yang berkaitan erat dengan eksekusi metode PjBL pada level pendidikan dasar. Sumber data dihimpun dari 25 artikel jurnal berskala nasional yang terbit dalam kurun waktu lima tahun terakhir (2020–2025). Proses seleksi materi acuan menerapkan standar inklusi yang ketat, meliputi studi empiris berbasis PjBL, melibatkan siswa SD sebagai partisipan utama, serta mengukur indikator performa belajar. Aktivitas bedah data diaplikasikan lewat tahapan identifikasi, reduksi, penilaian kritis, hingga penyimpulan akhir terhadap seluruh referensi terpilih. Konklusi dari telaah ini membuktikan bahwa skema pembelajaran berbasis proyek tersebut membawa andil positif sekaligus bermakna bagi eskalasi hasil belajar anak didik. Intervensi PjBL terbukti menstimulasi kecakapan kognitif, gairah belajar, daya cipta, ketajaman berpikir kritis, kecakapan berinteraksi, sinergi kelompok, hingga ketangkasan dalam mengurai masalah. Di samping itu, efektivitas PjBL melampaui performa pola instruksi konvensional karena sifatnya yang dinamis, kontekstual, serta menempatkan siswa sebagai poros utama pembelajaran. Ditinjau dari parameter hasil belajar, lompatan paling signifikan dijumpai pada dimensi kognisi, yang kemudian disusul oleh penguatan bidang afektif serta psikomotorik. Berdasarkan temuan tersebut, model PjBL sangat direkomendasikan sebagai opsi strategi pedagogi progresif guna menyokong target Kurikulum Merdeka serta penguatan kompetensi abad ke-21 di ekosistem sekolah dasar.